PERAN DAN KOMPETENSI KEMAMPUAN PEMERINTAH TERHADAP PERKEMBANGAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI KOTA BATAM - Ade Parlaungan Nasution (Universitas Riau Kepulauan, 2014)
This research had a purpose To (1). analysed and proved the influence of the government capacity on the development of Batam City economics (2) To analyse and prove the influence of the government capacity on the level of welfare in the Batam City(3) To measure and prove the influence of the Development of economics on Welfare of the Kota Batam Data Community that in used in this research was the secondary quantitative data.The data was analysed by using the PLS analysis (partial Least Square).Results that were received were the Goverment Capacity of the Batam City to be influential significant towards Welfare of the community was to be accepted.Results of the PLS analysis produced the path coefficient 0.0500 with p-value = 0,000, therefore was significant.This means that was gotten by the influence of the significant negativebetween the Level of the government capacity towards welfare of the community.The level of the Development of Kota Batam Economics was influential significant towards the level of welfare of the community was to be accepted.Results of the PLS analysis produced the path coefficient 0.0500 with p-value = 0,000, therefore significant.This means that was gotten by the significant influence between the level of the development of economics towards the level of welfare of the City communityBatam.Level the government capacity was influential significant towards the level of the development of economics.Results of the PLS analysis produced the path coefficient 0.0991 with p-value = 0,0001, therefore was severed significant.